Nanoporosity of Alumina Surfaces Induces Different Patterns of Activation in Adhering Monocytes/Macrophages - Natalia Ferraz; Jaan Hong; Matteo Santin; Marjam Karlsson Ott (International Journal of Biomaterials)
The present study shows that alumina nanotopography affects monocyte/macrophage behavior. Human mononuclear cells cultured on alumina membranes with pore diameters of 20 and 200 nm were evaluated in terms of cell adhesion, viability, morphology, and release of proinflammatory cytokines. After 24 hours, cell adhesion was assessed by means of light microscopy and cell viability by measuring LDH release. The inflammatory response was evaluated by quantifying interleukin-1β and tumour necrosis factor-α. Finally, scanning electron microscopy was used to study cell morphology. Results showed pronounced differences in cell number, morphology, and cytokine release depending on the nanoporosity. Few but highly activated cells were found on the 200 nm porous alumina, while relatively larger number of cells were found on the 20 nm porous surface. However, despite their larger number, the cells adhering on the 20 nm surface exhibited reduced pro-inflammatory activity. The data of this paper implies that nanotopography could be exploited for controlling the inflammatory response to implants.